Reactive chemistry via the redox switching of microdroplets of 4-nitrophenyl nonyl ether in the presence of aqueous electrolytes - Wain, A; Lawrence, N; Greene, P; Wadhawan, J; Compton, R (2003)
The voltammetry of 4-nitrophenyl nonyl ether is studied in the form of microdroplets immobilised on a basal plane pyrolytic graphite electrode surface immersed into aqueous electrolytes. A complex series of electron and proton transfers are voltammetrically initiated at the three-phase junction comprising electrode|4-nitrophenyl nonyl ether|aqueous electrolyte. In buffered aqueous solutions at acidic pH values, it is shown that 4-nitrophenyl nonyl ether is reduced in a six-electron, six-proton step to the corresponding aniline; at alkaline pH values, two voltammetric waves are present, attributed to a four-electron, four-proton wave followed by a two-electron, two-proton signal. In addition, alkali-metal cation insertion is shown to compete with proton addition to counter the negative charge injected into the organic phase.